TINJAUAN GAYA TSUNAMI PADA JEMBATAN KRUENG RABA - Mahfuz Mahfuz; Mochammad Afifuddin; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2020)
Aceh Province is located in one of the earth's fault lines in Indonesia, which is an area prone to earthquakes and the potential for a tsunami disaster. Therefore, any planning of structures located on the coast must consider the potential for a tsunami to obtain a strong structure to withstand the forces affected by the tsunami. During the 2004 tsunami, many bridges were carried away by the tsunami. Both bridges made of concrete, as well as steel frame bridges, such as the Krueng Raba steel frame bridge, Lhoknga, the Krueng No bridge, the Meunasah Kulam bridge, and several other bridges. This study aims to analyze and calculate the force and load effects of the tsunami on the structure of one of these bridges, namely the Krueng Raba steel frame bridge, Lhoknga. The force and load of the tsunami effect (Ts) will be analyzed by adopting the Guidelines for Design of Structures for Vertical Evacuation from Tsunamis, 2012, namely: (1) hydrostatic force; (2) buoyant forces; (3) hydrodynamic forces; (4) impulsive forces; (5) debris impact forces; (6) debris damming forces; (7) lift force; and (8) additional gravity load from water retained on the bridge floor. From the results of this study, it is shown that each of the tsunami forces acting on the crew-raba Lhoknga bridge at the minimum tsunami height variable, 11 meters, which is the initial height of the tsunami touching the bridge's superstructure are: 94.866 KN hydrodynamic force; 142,299 KN thrust; 133,810 KN debris impact force; 14,244 KN debris dam force, and 34,018 KN lift force. Meanwhile, the maximum tsunami height variable, 25 meters, is 24634.934 KN hydrodynamic force; 36952,400 KN thrust; 720,591 KN collision force; 3698,939 KN debris blocking force; and 986,519 KN lift styles. The results of the analysis using computational methods, by inputting the magnitude of the tsunami forces to the bridge model, it can be seen that the ability of the Krueng Raba, Lhoknga steel frame bridge to withstand the forces and loads caused by the tsunami only up to a height of 14 meters.